The importance of brick and mortar stores in the development of specialized running e-commerce - Kopková, Ivana; Stříteský, Václav; Poštulka, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
E-commerce is increasing rapidly, and the shopping behaviour of customers is changing. During the last years, the popularity of running among Czechs has increased significantly. This master’s thesis aims to investigate the purpose and find the best use of the brick and mortar store for the selected specialized running e commerce retailer. Secondary aim is to understand the shopping behaviour of runners in the Czech Republic and their attitude to brick and mortar store with running equipment. On top of that, author aims to analyse the current state of the sportswear market both in the Czech Republic and worldwide. The analyses of collected data from the researches reveal the importance of having brick and mortar store in the case of the specialized e-commerce retailer and the recommendations are given to selected e-commerce retailer.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses